2022
DOI: 10.1186/s12913-022-08036-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeat hospital transfers among long stay nursing home residents: a mixed methods analysis of age, race, code status and clinical complexity

Abstract: Background Nursing home residents are at increased risk for hospital transfers resulting in emergency department visits, observation stays, and hospital admissions; transfers that can also result in adverse resident outcomes. Many nursing home to hospital transfers are potentially avoidable. Residents who experience repeat transfers are particularly vulnerable to adverse outcomes, yet characteristics of nursing home residents who experience repeat transfers are poorly understood. Understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…We also restricted our analyses to the first SNF stay, which limits our ability to study differences in care provided by ACOs and Non-ACOs for the specific population of patients who require repeated transfers17 between nursing facilities and acute-care hospitals. Although we did account for important case-mix components that have been previously noted to be more common in patients requiring repeated transfers (eg, age, race), our claims-only based study was unable to capture other important characteristics (eg, code status, changes in goals of care, patient or family requests) that require qualitative methods to assess 17. Finally, ACO-attributed patients may select higher-quality SNFs, with more experienced nurse practitioners delivering care for reasons unrelated to their attribution status (eg, fewer comorbidities).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also restricted our analyses to the first SNF stay, which limits our ability to study differences in care provided by ACOs and Non-ACOs for the specific population of patients who require repeated transfers17 between nursing facilities and acute-care hospitals. Although we did account for important case-mix components that have been previously noted to be more common in patients requiring repeated transfers (eg, age, race), our claims-only based study was unable to capture other important characteristics (eg, code status, changes in goals of care, patient or family requests) that require qualitative methods to assess 17. Finally, ACO-attributed patients may select higher-quality SNFs, with more experienced nurse practitioners delivering care for reasons unrelated to their attribution status (eg, fewer comorbidities).…”
Section: Discussionmentioning
confidence: 99%
“…Our use of only the index SNF stay was motivated by concerns that patients with repeated SNF stays would be more likely to be complex in characteristics not well described in claims data. For example, although we did account for important case-mix components that have been previously noted 17 to be more common in patients requiring repeated transfers (eg, age, race), our claims-only based study was unable to capture other important characteristics (eg, code status, changes in goals of care, patient or family requests) that have required qualitative methods to assess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous researchers, our study found that family insistence on transferring the resident to the hospital was an issue, 13 including repeat transfers that were potentially avoidable. 14 Because this Decision Guide originated from a person-centered research approach focused on resident and family perspectives 16 regarding their understanding and misunderstandings about resident transfers and nursing home care, it is unlike other clinically focused tools for staff use, such as the INTERACT Tools 11 and the newer Avoidable Transfer Tool developed to retrospectively identify factors influencing resident transfers and how to avoid them in the future. 27 Working with residents and family members is integral in reducing readmission rates.…”
Section: Reflections On Existing Evidencementioning
confidence: 99%
“…12 Notably, of the 650 hospital transfers that were evaluated during this project, 111 (17%) were due to resident and family insistence, 13 a previously neglected factor contributing to these preventable readmissions that occur relatively frequently. 14 To address this heretofore neglected aspect of avoidable hospitalizations, we adopted a person-centered research approach 15,16 beginning with a series of 271 in-depth interviews with 96 nursing home residents, 75 families, and 100 staff and providers from 18 nursing homes in South Florida. Based upon the interview results, an interdisciplinary team created an evidence-based decision aid, Go to the Hospital or Stay Here?…”
Section: Introductionmentioning
confidence: 99%